RESIKO DAN MITIGASI BENCANA GEMPA TEKTONIK DI KABUPATEN KONAWE - Tamburaka, Erni (EDUTECH CONSULTANT, 2019)
This study aims to determine the level of seismicity in Konawe Regency, to produce a map of the distribution of threat zones, vulnerability, capacity and risk of tectonic. Disaster (PRB) tectonic earthquake. Analysis of seismicity levels using statistical methods, namely by using the likelihood statistical method obtained from the relationship of earthquake magnitude to earthquake frequency according to B. Guttenberg and C.F. Richter (1954). To produce a zone map of the spread of threats, vulnerabilities, capacities and disaster risks, earthquake tectonics use spatial data analysis methods with geographic information system (GIS) applications and are mapped using GIS Arcview software. The results showed the highest level of seismicity was in area II, the lowest was in area II, namely District of Routa. Based on the tectonic earthquake risk map in the figure, it is known that around 30.49% of the Konawe District area has a high level of risk of tectonic earthquakes), 32.83% is an area of ​​moderate risk (Routa), and 36.68% (Latoma). , Asinua, Unaaha, Puriala, Lalonggasumeeto) are areas that are not at risk of tectonic earthquakes.